The The Influence of Intensity of Accessing the TikTok Account @canro.simarmata on Interest in Mountain Climbing among Followers - Prasetyo, Muhammad Iqbal; Nuur Rasyid, Haryadi Arief (Jogjakarta Communication Conference (JCC), 2025)
This study examines how frequent access to the TikTok account @canro.simarmata affects the interest in mountain hiking among its followers. This study aims to determine whether consistent exposure to hiking-related content on TikTok affects followers' desire to engage in hiking activities. Using quantitative methods and a survey approach, data were collected from 400 respondents through a questionnaire. The analysis shows a significant influence effect between the intensity of access and the interest in hiking. The results of the determination coefficient test show that the variable of the intensity of accessing the TikTok account @canro.simarmata has an influence of 55.8% on the interest in mountain hiking among followers. This finding suggests that digital media content can shape outdoor activity preferences through frequent and interesting exposure.